Application of Electrical Conductivity (EC), Temperature and pH Sensors on IoT Based Red Ginger TOGA (Zingiber Officinale Var Rubrum) Planting Media - Arinie, Farida; Qotrunada, Savira Balqis; Hadiwiyatno, Hadiwiyatno (Politeknik Negeri Malang, 2023)
The red ginger plant is a type of rhizome plant which is one of the spices that are needed in Indonesia. The number of requests for red ginger requires the right planting media composition. Charcoal husks and manure are often used as mixed materials, especially those that cultivate plants in the bottom or polybags. An important parameter in the farming system is Electrical Conductivity (EC), temperature and pH. The degree of acidity or pH of the soil is very influential on the growth of a plant with a value between 6.5 to 7.5. The room temperature for red ginger plants is good with a range of 22-35°C. The TDS meter value in PDAM water is good at 100 ppm but the smaller the TDS value the better the water conductivity. The results of the sample testing 1, 2 and 3 of the soil pH value are at 5.9 to 6.4, this has a large impact of plant nutrient not available, so that Plant growth is disrupted. The TDS value is in the value of 87 to 95 shows the conductivity of water during the trial period in good condition. The temperature value of the space is in the range of 20-34°C which the temperature value is in the right condition. Making IoT-Based Application in Red Ginger Plants can help find out the good value of water conductivity, room temperature and soil pH in planting red ginger plants that can be monitored through the application.